(untitled) (Bangladesh Journal of Botany, 2008)
Four species of the genus Kallymenia J. Ag. such as K. cribrosa Harvey, K. rosea Womersley & Norris, K. rubra Womersley & Norris K. tasmanica Harvey have been reported for the first time from St. Martin’s Island, Bangladesh. Key words: Seaweeds, Marine algae, Kallymenia spp., St. Martin’s Is., Bangladesh doi:10.3329/bjb.v37i2.1726 Bangladesh J. Bot. 37(2): 173-178, 2008 (December)